A low-profile consolidated metastructure for multispectral signature management. (31st January 2022) - Gupta, Nitish Kumar; Singh, Gaganpreet; Wanare, Harshawardhan; Ramakrishna, S Anantha; Srivastava, Kumar Vaibhav; Ramkumar, J
Abstract: This work pertains to the design, numerical investigation, and experimental demonstration of an optically transparent, lightweight, and conformable metastructure that exhibits multispectral signature management capabilities despite its extremely low-profile configuration. In comparison to the existing hierarchical approaches of designing multispectral stealth solutions, attention has been paid to accommodate the conflicting requirements of radar and infrared (IR) stealth using a single metasurface layer configuration, which required a few constraints to be incorporated during the design stage to ensure compatibility. This methodology promulgates the desired multispectral response with minimal manufacturing footprint and facilitates an efficient integration with the other existing countermeasure platforms. The resulting design exhibits a polarization-insensitive and incident angle stable broadband microwave absorption with at least 90% absorption ranging from 8.2 to 18.4 GHz. Concomitantly it also exhibits an averaged IR emissivity of 0.46 in the 8–14 µ m long-wave IR regime, along with high optical transparency (71% transmission at 632.8 nm). Notably, the total thickness of the metastructure stands at 0.10 λ L ( λ L corresponds to the wavelength at lowest frequency). The metastructure has been fabricated with indium tin oxide coated polyethylene terephthalate sheets, on which the frequency selective pattern is machined using Excimer laser micromachining, and the performances are verified experimentally. Furthermore, a hybrid theoretical model has been developed that not only provides crucial insights into the operation of metastructure but also presents a methodical semi-analytical approach to design.